Spiritual well-being and mental health among students: Evidence from Indonesia - Muli Noer (University of Johannesburg, 2023)
This research investigates whether and how religiosity (for example, spiritual well-being) influences the mediator variables (student attitude, subjective norm, and behavioural control) in the education field based on the Theory of Planned Behaviour (TPB). It also examines how these mediator variables affect students' mental health. 572 students were recruited for a survey study, and structural equation modeling (SEM) was used to test the research hypotheses. The empirical results indicate that spiritual well-being has significant and positive effects on students' attitudes, subjective norms, and behaviour, subsequently influencing their mental health. Furthermore, the mediator variables (for example, students' attitude, subjective norm, and behaviour) partially mediate religiosity and mental health. The results of this study suggest that regulators should collaborate with parents, schools, and teachers to develop a suitable curriculum, based on religiosity principles, which correlates with the current situation.